Cost-effectiveness analysis of newborn screening for sickle-cell disease in Spain. (2nd June 2016) - Castilla-Rodríguez, Iván; Cela, Elena; Vallejo-Torres, Laura; Valcárcel-Nazco, Cristina; Dulín, Elena; Espada, Mercedes; Rausell, Dolores; Mar, Javier; Serrano-Aguilar, Pedro
ABSTRACT: Objectives: This study assesses the cost-effectiveness of adding sickle-cell disease (SCD) to the Spanish newborn screening (NBS) program, and explores the sensitivity of the results to key model parameters. Methods: A discrete event simulation model was developed that compared NBS for SCD versus clinical detection. The model followed a simulated cohort of newborns for 10 years, and estimated the impact in costs and life expectancy of prophylactic treatments established after early detection. Probabilistic, one-way and two-way sensitivity analysis were performed. Results: NBS was found to be more costly and more effective than clinical detection of SCD. The estimated incremental cost per life year (LY) gained was 34, 169.46 €/LY. This result was very sensitive to the cost of the screening test, the birth prevalence and the proportion of severe cases among the affected children. Conclusions: There is uncertainty regarding the cost-effectiveness of NBS for SCD in the Spanish context. Our base case estimate of the cost per LY gained lies near the 30, 000€/LY commonly cited in Spain.